The happy sleeper : the science-backed guide to helping your baby get a good night's sleep--newborn to school age - Turgeon, Heather (Jeremy P. Tarcher/Penguin, a member of Penguin Group (USA), 2014)
"An urgent message for all sleep-deprived parents: You don't have to suffer through stressful strategies such as "cry-it-out" to get your child's sleep schedule on track. There's another way! Parents spend a great deal of energy coaxing, singing, and swinging their children to sleep. Yet over time, all that cajoling can actually have the opposite of its desired effect. Most parents do what works today but don't notice when it's no longer needed tomorrow, and then push harder when it becomes a hindrance the day after that. The Happy Sleeper shows parents how to avoid and undo cumbersome sleep habits. Mindfulness-the practice of using focused attention and being present and open-serves as the foundation for the techniques in this book. Using these methods in a thoughtful and loving way, parents can guide their children in learning how to soothe themselves to sleep-putting little kids (and the whole family!) on track to a full night's sleep. The Happy Sleeper features a foreword by neuropsychiatrist and popular parenting expert Dr. Daniel Siegel, author of Parenting from the Inside Out and the New York Times bestseller Brainstorm. "--